Internet das coisas e as relações de consumo : a necessidade de ressignificação e efetividade do direito à privacidade - Azambuja, Mariana Menna Barreto (2021)
The evolution of technology has left Law operators more and more attentive to the new configurations of legal relations that have been changing year after year. For that, it is necessary to modernize some classic concepts that no longer have space in the scenario in which we live today, within what some call the Fourth Industrial Revolution. Among the most modern technologies that has been increasingly dominating the space among consumers is the Internet of Things. The Internet of Things brings a paradox to everyone's life, since on the one hand we have extraordinary information and facilities at our disposal, but, on the other hand, we place ourselves at the mercy of a phenomenon still unprecedented in its limits and reach. The objective of this thesis will be to understand the benefits and challenges of this technology for consumers and how the study, as well as the consequent reframing of the concept of privacy, is necessary for the matter to have fair treatment in the current system. In addition, it is intended to propose a form of labeling in the scope of privacy to also bring effectiveness to this right.